Digital Literacy in Islamic Elementary Education: Transforming Religious Character Building in Rural Madrasah Ibtidaiyah - Galuh Fadella; Musammah Al Jaenab; Jini Wahyedi; Maryam; Dalima Septiria (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
The digital era presents both challenges and opportunities for Islamic educational institutions in rural areas. This study aims to explore the integration of digital literacy in the process of building students' religious character in rural Madrasah Ibtidaiyah (MI). Using a descriptive qualitative method with a case study approach, this research highlights how the use of information technology can transform conventional moral learning methods into more adaptive and interactive ones. The results indicate that digital literacy is not merely the mastery of technical devices, but a means to instill Islamic values through educative digital content. Despite facing infrastructural limitations in rural areas, collaboration between teachers, parents, and the appropriate use of digital media has proven effective in strengthening students' religious character, such as honesty in cyberspace and digital responsibility. This transformation demonstrates that rural madrasahs are capable of adapting to modernity without losing the essence of faith-based character education.